The Influence Of Tax Contributions And Tax Retributions On Original Income Of District Regions In Indonesia For The 2017-2022 Period - Edtri, Dini Zalzabila; Pakawaru, Muhammad Ilham (Adpebi Science Series, 2024)
Taxes and tax levies in Indonesia play a central role in supporting Local Original Revenue (PAD), which is the main pillar of funding for local governments to implement various development programs and provide public services. The involvement of taxes and levies as a source of local revenue shows its strategic significance in supporting the sustainability of the local economy. The purpose of this study is to investigate the dynamics of tax and tax levy contributions to Local Original Revenue at the district level in Indonesia during the period 2017-2022. A quantitative approach is used to analyze related data in exploring these dynamics. Research findings show that tax contributions (Inpad) and tax levies (Inretda) have a significant relationship with Local Original Revenue. The regression model used showed an excellent degree of adjustment, with an R-squared of 0.8514 and an adjusted R-squared of 0.8512, as well as a statistically significant F-. From a multicollinearity perspective, Variance Inflation Factor (VIF) analysis shows that regression models do not suffer from serious multicollinearity problems, and the coefficient estimation results can be considered reliable. This finding reflects that tax contributions and tax levies do not only focus on revenue aspects alone, but also reflect the close relationship between the tax sector and regional financial stability. In addition, the findings of this study provide empirical support to the important role of taxes and tax levies in strengthening Local Original Revenue and, more broadly, regional finance in Indonesia. The implications of these findings can guide local government policies in designing more effective tax strategies, as well as raising public awareness of their contributive role in supporting development and public services at the local level. Therefore, this research is expected to make a positive contribution in improving regional financial sustainability and supporting sustainable economic growth in Indonesia.